(untitled) (Journal of the College of Basic Education, 2023)
The Holy Qur’an, in all its subjects, seeks to develop and preserve the individual in all circumstances and in all aspects of his life, based on his being God’s successor on earth. Saleh develops himself the Holy Quran.Keywords: sustainable development - self-development - building societies